The influence of absorbed solar radiation by Saharan dust on hurricane genesis - Bretl S; Reutter P; Raible CC; Ferrachat S; Poberaj CS; Revell LE; Lohmann U (Journal of Geophysical Research: Atmospheres, 2018)
To date, the radiative impact of dust and the Saharan air layer (SAL) on North Atlantic hurricane activity is not yet known. According to previous studies, dust stabilizes the atmosphere due to absorption of solar radiation but thus shifts convection to regions more conducive for hurricane genesis. Here we analyze differences in hurricane genesis and frequency from ensemble sensitivity simulations with radiatively active and inactive dust in the aerosol-climate model ECHAM6-HAM. We investigate dust burden and other hurricane-related variables and determine their influence on disturbances which develop into hurricanes (developing disturbances, DDs) and those which do not (nondeveloping disturbances, NDDs). Dust and the SAL are found to potentially have both inhibiting and supporting influences on background conditions for hurricane genesis. A slight southward shift of DDs is determined when dust is active as well as a significant warming of the SAL, which leads to a strengthening of the vertical circulation associated with the SAL. The dust burden of DDs is smaller in active dust simulations compared to DDs in simulations with inactive dust, while NDDs contain more dust in active dust simulations. However, no significant influence of radiatively active dust on other variables in DDs and NDDs is found. Furthermore, no substantial change in the DD and NDD frequency due to the radiative effects of dust can be detected.